THE WEST? WHICH WEST? Reflections About the West From the Perspective of Hispanidad - Miriam Fernández Calzada (Ибероамериканские тетради)
If we look at the history of mankind as a whole, we can see how the different human groups or peoples have tended to group together under the roof of great civilizations or socio-cultural supersystems. These supersystems determine the movement in the socio-cultural ocean of all the other countries or peoples that make them up. One of the basic pillars on which each of these socio-cultural systems or civilizations rests, as Russian scientist Nikolay Danilevski established long ago, is determined by religion, which to a great extent conditions the worldview of that civilization and its energy. The supersystem that constitutes today’s West has an Anglo-Saxon-Protestant root base, a West that has, however, undergone a pathological overdevelopment that is blocking and preventing the development of other forms of civilization.However, the first version of the West was not the Anglo-Saxon-Protestant, but the Hispano-Catholic one. The article seeks to reflect on the possibility of returning to this first version of the West, perhaps more inclusive and open to the simultaneous presence of alternative supersystems as opposed to the imposing and annihilating character of the Anglo-Saxon West. The result of this first notion of the West is what we can call «Hispanidad». Given the diffuse nature of this concept, a review of some of the definitions given by Spanish-speaking thinkers at different times is proposed, with the aim of pointing out possible ways of developing an updated version of this idea.